Circulating sphingolipids in relation to cognitive decline and incident dementia: The Cardiovascular Health Study. - Moseholm, Kristine F; Cronjé, Héléne T; Koch, Manja; Fitzpatrick, Annette L; Lopez, Oscar L; Otto, Marcia C de Oliveira; Longstreth, W T; Hoofnagle, Andrew N; Mukamal, Kenneth J; Lemaitre, Rozenn N; Jensen, Majken K (Alzheimers Dement (Amst), 2024)
INTRODUCTION: Whether circulating levels of sphingolipids are prospectively associated with cognitive decline and dementia risk is uncertain. METHODS: We measured 14 sphingolipid species in plasma samples from 4488 participants (mean age 76.2 years; 40% male; and 25% apolipoprotein E ( ε4 allele carriers). Cognitive decline was assessed annually across 6 years using modified Mini-Mental State Examination (3MSE) and Digital Symbol Substitution Test (DSST). Additionally, a subset of 3050 participants were followed for clinically adjudicated dementia. RESULTS: Higher plasma levels of sphingomyelin-d18:1/16:0 (SM-16) were associated with a faster cognitive decline measured with 3MSE, in contrast, higher levels of sphingomyelin-d18:1/22:0 (SM-22) were associated with slower decline in cognition measured with DSST. In Cox regression, higher levels of SM-16 (hazard ration [HR] = 1.24 [95% confidence interval [CI]: 1.08-1.44]) and ceramide-d18:1/16:0 (Cer-16) (HR = 1.26 [95% CI: 1.10-1.45]) were associated with higher risk of incident dementia. DISCUSSION: Several sphingolipid species appear to be involved in cognitive decline and dementia risk. HIGHLIGHTS: Plasma levels of sphingolipids were associated with cognitive decline and dementia risk.Ceramides and sphingomyelins with palmitic acid were associated with faster annual cognitive decline and increased risk of dementia.The direction of association depended on the covalently bound saturated fatty acid chain length in analysis of cognitive decline.